Associations between family structure and young people's physical activity and screen time behaviors - Amund Langøy; Otto R. F. Smith; Bente Wold; Oddrun Samdal; Ellen M. Haug (BMC, 2019)
Abstract Background Identifying factors that can influence young peoples' physical activity and sedentary behaviors is important for the development of effective interventions. The family structure in which children grow up may be one such factor. As the prevalence of single parent and reconstituted families have increased substantially over the last decades, the objective of this study was to examine whether these family structures are differentially associated with young people's MVPA, participation in organized sports and screen-time activities (screen-based passive entertainment, gaming, other screen-based activities) as compared to traditional nuclear families. Methods The data stem from the 2013/2014 "Health Behaviour in School- aged Children (HBSC) study". A large Norwegian sample of 11-16 years old students (n = 4509) participated. Cluster-adjusted regression models were estimated using full information maximum likelihood with robust standard errors (MLR). Results After adjusting for covariates, living with a single parent was negatively associated with days/week with 60 min MVPA (b = −.39, 95%CI: −.58, −.20), and positively associated with hours/weekday of total screen time (b = .50, 95%CI: .08, .93). Young people living with a single parent were also more likely to report no participation in organized sports (OR = 1.40, 95%CI: 1.09, 1.79). Living in a reconstituted family was negatively associated with days/week with 60 min MVPA (b = −.31, 95%CI: −.53, −.08), and positively associated with hours/weekday of total screen time (b = .85, 95%CI: .37, 1.33). For all outcomes, the interaction effects of family structure with sex, and with having siblings were not statistically significant. For material affluence, a significant interaction effect was found for participation in organized sports (χ2 [4] =13.9, p = .008). Those living in a reconstituted family with low or high material affluence had an increased risk for not participating in organized sports whereas those with medium material affluence did not. Conclusion This study suggests that living with a single parent or in reconstituted families was unfavorably associated with physical activity, sport participation and screen-based behaviors among Norwegian youth. The findings indicate that family structure could be an important factor to take into account in the development and testing of interventions. More in-depth research is needed to identify the mechanisms involved.